2001
DOI: 10.1177/104063870101300204
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Purified Protein Derivatives and Effect of Skin Testing on Results of a Commercial Gamma Interferon Assay for Diagnosis of Tuberculosis in Cattle

Abstract: Abstract. Purified protein derivatives (PPD) prepared in the USA were compared with those prepared in Australia by a private company (CSL Veterinary) for use with a commercial gamma interferon (␥-IFN) assay for diagnosis of bovine tuberculosis. The effect of skin testing on results of the ␥-IFN assay was determined, and results were compared when blood samples were stimulated with PPD within 2 hours and after 24 hours of sample collection. Twenty cattle that were sensitized by subcutaneous injection of heat-ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
5
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 13 publications
4
58
5
2
Order By: Relevance
“…In this case, this common population was also small (40.9%). Therefore, and in agreement with other authors [13,28,32,39,45], the detection of the maximum number of infected animals is achieved by the combination of both tests. Both tests were complementary also in the way that the IDTB test performed better during the first part of the trial, while the IFN-γ test was the only method that detected the infected animals at the second part of the study (it detected the M. bovis culture positive cattle that failed to react to the IDTB test).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this case, this common population was also small (40.9%). Therefore, and in agreement with other authors [13,28,32,39,45], the detection of the maximum number of infected animals is achieved by the combination of both tests. Both tests were complementary also in the way that the IDTB test performed better during the first part of the trial, while the IFN-γ test was the only method that detected the infected animals at the second part of the study (it detected the M. bovis culture positive cattle that failed to react to the IDTB test).…”
Section: Discussionsupporting
confidence: 91%
“…Since the performance of the tests was being compared on the same animals, they were tested simultaneously to avoid the interference of one test with the other [30,41]. These tests were repeated 8 times over a 3.5-year period, avoiding the summer and the last pregnancy seasons.…”
Section: Design Of the Studymentioning
confidence: 99%
“…2B, day 96). In contrast, cattle sensitized to M. bovis antigens exhibit increased IFN-␥ responses for 3 to 28 days after PPD administration for CCT (31). In other studies, using M. bovisinfected cattle, results of IFN-␥ tests were not affected by PPD administration for skin testing (6,23).…”
Section: Discussionmentioning
confidence: 90%
“…The IFN-c assay has been widely employed for the diagnosis of tuberculosis 10,25 and paratuberculosis 21 in domestic ruminants. In cervids, in which the cytokine has a different structure, some authors have reported the use of this test in M. bovis experimentally infected or vaccinated animals, obtaining good results in different phases of the infection.…”
Section: <!?Show "Fnote_aff1"$^!"content-markup(/author-grp[1]/aff|/author-grp[1]/dept-list)>mentioning
confidence: 99%